IMF Survey, Volume 32, Issue 08. (IMF Survey; IMF Survey ;, 2003)
Speaking at the Thirty-Third Washington Conference of the Council of the Americas on April 29, IMF Managing Director Horst Kohler expressed optimism about Latin America's growth prospects. Despite difficult economic times, he said, the people have indicated no desire to return to past authoritarian regimes, and several countries have recently reaffirmed their commitment to a market-based system. A summary of Kohle's address, delivered at the U.S. Department of State, follows.